2019
DOI: 10.1101/556043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical flow analysis reveals that Kinesin-mediated advection impacts on the orientation of microtubules in theDrosophilaoocyte

Abstract: 21The polar orientation of microtubule networks is exploited by molecular motors, such as kinesins, to 22 deliver cargoes to specific intracellular destinations, and is thus essential for cell polarity and cell 23 function. Reconstituted in vitro systems have largely contributed to the current understanding of the 24 molecular framework, regulating the behaviour of single microtubule filaments. In cells however, 25 microtubules are subjected to a variety of different biomechanical forces that might impact on t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Kinesin-1 has been shown to interfere directly with MT organization (Daire et al, 2009; Drechsler et al, 2020; Nieuwburg et al, 2017), especially through its ability to crosslink MTs (Lu et al, 2016; Metzger et al, 2012). Hence, we wondered if the nuclear migration defects observed in absence of Khc and Klc could be explained by defects in MT organization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kinesin-1 has been shown to interfere directly with MT organization (Daire et al, 2009; Drechsler et al, 2020; Nieuwburg et al, 2017), especially through its ability to crosslink MTs (Lu et al, 2016; Metzger et al, 2012). Hence, we wondered if the nuclear migration defects observed in absence of Khc and Klc could be explained by defects in MT organization.…”
Section: Resultsmentioning
confidence: 99%
“…It is quite striking that the delay for nuclear migration does not gradually appear after stage 7, as we would expect from a simple slowing down of the process, but is sharply occurring at stage 9. We and others have previously shown that the MT network in the oocyte undergoes dramatic rearrangement at stage 9 to organize bundles at the cell cortex (Drechsler et al, 2020; Januschke et al, 2006; Lu et al, 2016; Nashchekin et al, 2016; Parton et al, 2011; Trong et al, 2015). At this stage, the MTs generate a cytoplasmic flow which sustains an advection-based transport corresponding to an active transport induced by fluid flow (Drechsler et al, 2017; Drechsler et al, 2020; Ganguly et al, 2012; Loiseau et al, 2010; Williams et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, optical flow methods have been used for the quantitative analysis of biological image sequences on cellular and subcellular level. See, for instance, [2,9,10,21,31,34,39,44,50]. While the concept is in practice well-suited for natural scenes, the use of the less restrictive continuity equation, which arises from mass conservation, can be more favourable in certain scenarios.…”
Section: Motivationmentioning
confidence: 99%